2018
DOI: 10.1159/000493662
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hypersensitivity Reactions During Hemodialysis

Abstract: Background/Aims: A recent alert from Spanish health authorities warned of a higher incidence of reported hypersensitivity reactions to hemodialysis membranes with polysulfone, in the 2017 review of acute reactions to dialyzers found only published reports in the 21st century on polysulfone and its derivatives. The aim is to assess/evaluate the current incidence and characteristics of hypersensitivity reactions in hemodialysis patients. Methods: A retrospective multicentre study in 9 Spanish hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Recently, a new-generation of dialyzer with a CTA membrane has entered the market, with an increase in the coefficient of ultrafiltration (72 mL/h/mm Hg) that allows online HDF [18]. In recent years, intolerance reactions (e.g., hypotension, desaturation) and allergies to synthetic dialyzers have been reported in a small percentage of patients [19][20][21], leading to the reintroduction of cellulose dialyzers such as CTA dialyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new-generation of dialyzer with a CTA membrane has entered the market, with an increase in the coefficient of ultrafiltration (72 mL/h/mm Hg) that allows online HDF [18]. In recent years, intolerance reactions (e.g., hypotension, desaturation) and allergies to synthetic dialyzers have been reported in a small percentage of patients [19][20][21], leading to the reintroduction of cellulose dialyzers such as CTA dialyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Hypersensitivity reactions to synthetic membranes continue to be observed [ 1 ] and typically disappear following replacement of the dialysis membrane with a different type, usually cellulose triacetate. Previous studies have described the low purification ability of β2-microglobulin and its limited use in online hemodiafiltration (OL-HDF) with symmetric cellulose dialyzers [ 2 ].…”
mentioning
confidence: 99%
“…Use of ethylene oxide for sterilizing dialyzers showed a decreasing trend and the more biocompatible polysulfone membranes became more widely used since the turn of the century. However, in 2018, Esteras et al .,[ 3 ] in a retrospective study in Spain across nine dialysis centers, found 37 (2.37%) reported cases out of 1561 patients in a two year period form August 2015 to August 2017 which is the around the same incidence as the two earlier described studies done more than 20 years back. Most of the reported reactions, after the year 2000, have been to polysulfone membranes, which is unsurprising, as it is the most widely used membrane now-a-days.…”
Section: Discussionmentioning
confidence: 58%